2005
DOI: 10.1189/jlb.1004564
|View full text |Cite
|
Sign up to set email alerts
|

Time-course expression of Toll-like receptors 2 and 4 in inflammatory bowel disease and homeostatic effect of VIP

Abstract: Toll-like receptor 2 (TLR2) and -4 mediate signals from a great variety of bacterial gut products, giving the host a panel of microbe-recognizing receptors. Under homeostatic conditions, TLRs act as protective receptors of the intestinal epithelium. When homeostasis is disrupted in diseases such as inflammatory bowel disease, TLR2 and -4 are deregulated. Our study demonstrates, by using a trinitrobenzene sulfonic acid-induced colitis model of Crohn's disease, the constitutive expression and the up-regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 33 publications
2
71
1
Order By: Relevance
“…However, clinical significance for TLR signaling in the pathogenesis of intestinal mucosa is suggested as patients with inflammatory bowel disease demonstrate an increase in the expression of TLR4 and TLR2 in the intestinal mucosa (75,78), and we have found that TLR4 expression is increased in experimental and human necrotizing enterocolitis (32). Sensitization of the intestinal mucosa through upregulation of TLRs also occurs in other diseases of intestinal inflammation, including inflammatory bowel disease and intestinal celiac disease (75,(79)(80)(81), suggesting a potential role in the injury response.…”
Section: Tlr-dependent Signaling In the Intestinal Mucosa: A Role In mentioning
confidence: 89%
“…However, clinical significance for TLR signaling in the pathogenesis of intestinal mucosa is suggested as patients with inflammatory bowel disease demonstrate an increase in the expression of TLR4 and TLR2 in the intestinal mucosa (75,78), and we have found that TLR4 expression is increased in experimental and human necrotizing enterocolitis (32). Sensitization of the intestinal mucosa through upregulation of TLRs also occurs in other diseases of intestinal inflammation, including inflammatory bowel disease and intestinal celiac disease (75,(79)(80)(81), suggesting a potential role in the injury response.…”
Section: Tlr-dependent Signaling In the Intestinal Mucosa: A Role In mentioning
confidence: 89%
“…VIP has been shown to regulate the expression and/or transactivating of transcription factors such as AP-1, NFκB, CREB and IRF-1 (13,14,34,36) and mediate the expression of chemokines, tumor necrosis factors, COX2, interleukin and toll-like receptors (8,15). TNFα showed tumor-promoting roles in previous studies and is regarded as a target in malignant cancer (21,37).…”
Section: Discussionmentioning
confidence: 99%
“…In peritonitis, VIP reduced recruitment of neutrophils, macrophages and lymphocytes via controlling the expression of transcription factors including AP-1, CREB and IRF-1 (12)(13)(14). Although inhibiting the expression levels of signaling pathways, VIP also induces the expression of toll-like receptors (TLRs) (15,16), indicating the multiple-effects on the immune system. In macrophages, similar to PACAP, VIP was able to bind to specific membrane receptors, including PAC1 and VPAC (17).…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids and noradrenalin are the classical examples of endogenous immunosuppressive agents produced, by the HPA axis and the sympathetic nervous system respectively, in response to stress or systemic inflammation [4,85]. Furthermore, a number of neuropeptides and hormones have emerged over recent years as potential candidates for the treatment of the unwanted immune responses, which occur in inflammatory and autoimmune disorders, by restoring immune homeostasis [46,85]. In this review, we will focus on the most recent developments regarding the effects on immune tolerance of the vasoactive intestinal peptide (VIP), a well-known anti-inflammatory neuropeptide, highlighting the effectiveness of this neuropeptide for the treatment of several immune disorders.…”
Section: Neuroimmune Crosstalk and Immune Tolerancementioning
confidence: 99%
“…Mounting evidence indicates that VIP acts via multiple mechanisms to counter inflammatory factors: a) VIP inhibits phagocytic activity, free radical production, adherence and migration of macrophages [12]; b) VIP reduces the production of inflammatory cytokines (tumor necrosis factor [TNFα], IL-12, IL-6 and IL-1β) and downregulates the expression of inducible nitric oxide synthase and the subsequent release of nitric oxide by macrophages, DCs and microglia [33,[35][36][37]55,66,87]; c) VIP limits the release of various chemokines and impairs signaling through chemokine receptors [18,25,36,53,55,72,95]; d) VIP stimulates the production of antiinflammatory cytokines such as IL-10, TGFβ1 and IL-1Ra [34,87]; e) VIP can decrease the co-stimulatory activity of antigen-presenting cells (APCs) toward antigen-specific T cells by downregulating the expression of the co-stimulatory molecules CD80 and CD86 [38]; and f) by reducing the expression of TLRs and associated molecules [29,46].…”
Section: Vip Acts As An Anti-inflammatory Agent In Innate Immunitymentioning
confidence: 99%